Media Framing of Disaster Governance in Indonesia: A Pan and Kosicki Analysis of Tempo’s “High Prestige of Emergency Disaster” - Alif Alqausar (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
This study examines how Tempo magazine framed the 2025 Sumatra flood disaster by applying the framing analysis model proposed by Pan and Kosicki. Using a qualitative approach, the research analyzes ten news articles published in Tempo’s cover story package “High Prestige of Emergency Disaster” (December 8, 2025 edition), encompassing editorial, political, environmental, and human-interest sections. The findings show that Tempo consistently constructed the disaster not as a purely natural event, but as a governance-driven crisis shaped by ignored early warnings, delayed political decision-making, and long-term environmental degradation. Through evaluative headlines, causal narrative structures, thematic coherence, and rhetorical strategies emphasizing moral responsibility, the magazine foregrounded state accountability and challenged official narratives that normalized the disaster as unavoidable. This framing positioned anticipatory failure, rather than emergency response alone, as the central problem in disaster management. The study contributes to framing theory by demonstrating the continued relevance of Pan and Kosicki’s model for analyzing complex disaster coverage and enriches scholarship on media, risk governance, and environmental communication in Indonesia. The findings highlight the role of critical journalism in shaping public understanding of disasters and underscore the importance of anticipatory governance and transparent risk communication in disaster-prone societies.